Specificity of creative correlation of historical truth and artistic fiction in the novel “The Passion of Taras” by Z. Lehkyi (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In the article aesthetic, composite peculiarities of documents (references, extractions, letters, direct fragments from literary works by T. Shevchenko) are considered and the role of creative fantasy in reproduction of events, personalities, phenomena in the novel by Z. Legkii «Tarasovi strasti» are disclosed.
Keywords: document; authenticity; fantasy; historical and fiction truth; fact; fiction biography